2016
DOI: 10.1155/2016/8605039
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus Open Omental Patch Repair for Early Presentation of Perforated Peptic Ulcer: Matched Retrospective Cohort Study

Abstract: Introduction. The aim of this study was to compare the outcomes between laparoscopic and open omental patch repair (LOPR versus OR) in patients with similar presentation of perforated peptic ulcer (PPU). The secondary aim was to evaluate the outcomes according to the severity of peritonitis. Methods. All patients who underwent omental patch repair at two university-affiliated institutes between January 2010 and December 2014 were reviewed. Matched cohort between LOPR and OR groups was achieved by only includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
7
22
0
Order By: Relevance
“…this difference might be attributed to the ease of process of peritoneal wash and larger volume of normal saline that can be used with open approach while it's to a little bit more difficult with laparoscopic approach and can't be as effective as in open approach. this was comparable to many other studies which showed same results 10,17,25 . Wound infection seen more frequent with open approach as seen in table IV.…”
Section: Discussionsupporting
confidence: 93%
“…this difference might be attributed to the ease of process of peritoneal wash and larger volume of normal saline that can be used with open approach while it's to a little bit more difficult with laparoscopic approach and can't be as effective as in open approach. this was comparable to many other studies which showed same results 10,17,25 . Wound infection seen more frequent with open approach as seen in table IV.…”
Section: Discussionsupporting
confidence: 93%
“…Included studies were published between 1996 and 2019. Five were RCTs [14][15][16][17][18] , three were prospective cohort studies [19][20][21] , and the other 15 studies used retrospective cohort or case-control designs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ( Table 1). All compared outcomes of laparoscopic versus open peptic ulcer repair.…”
Section: Resultsmentioning
confidence: 99%
“… 8 10 Moreover, research has revealed that establishing pneumoperitoneum for intestinal decompression in patients with intestinal obstruction improved treatment efficacy and led to better clinical outcomes including shorter durations of surgery, less intraoperative blood loss, lower postoperative pain scores, and shorter lengths of hospital stay. 11 13 …”
Section: Discussionmentioning
confidence: 99%